2012
DOI: 10.1007/s13402-012-0118-0
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of klotho expression induces apoptosis and autophagy in hepatocellular carcinoma cells

Abstract: Klotho is a tumor suppressor that, through the regulation of IGF-1R phosphorylation and subsequent activation of downstream Akt-p70S6K and ERK signaling, regulates HCC tumor cell proliferation, apoptosis, autophagy and invasion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
41
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 27 publications
2
41
0
2
Order By: Relevance
“…IGF1R simulates colon cancer cell growth via activation of the PI3K/AKT pathway (29). Our present study also demonstrated that overexpression of KL could downregulate the expression of IGF1R, p-PI3K and p-AKT in colon cancer cells, suggesting that KL might regulate IGF1R and subsequently activate the downstream PI3K/Akt signaling pathway (23,25).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…IGF1R simulates colon cancer cell growth via activation of the PI3K/AKT pathway (29). Our present study also demonstrated that overexpression of KL could downregulate the expression of IGF1R, p-PI3K and p-AKT in colon cancer cells, suggesting that KL might regulate IGF1R and subsequently activate the downstream PI3K/Akt signaling pathway (23,25).…”
Section: Discussionsupporting
confidence: 72%
“…Exogenous KL gene expression significantly inhibits cell growth and invasion, and induces cell apoptosis and autophagy in HCC (23)(24)(25). Inversely, some studies have revealed a novel oncogenic function of KL of in promoting tumor migration and invasion via activation of VEGFR2/PAK1 signaling (26).…”
Section: Discussionmentioning
confidence: 99%
“…Xie et al (36) measured mRNA and protein expression levels of α-Klotho in 64 HCC tumor tissues using real-time polymerase chain reaction and immunohistochemistry, respectively, demonstrating that a loss of α-Klotho expression in HCC cells was a predictive factor for the poor prognosis of the disease. Similarly, Shu et al (37) reported that exogenous expression of the Klotho gene significantly inhibited the proliferation of HCC cells, induced HCC cell apoptosis and decreased HCC cell migration, using a Matrigel invasion chamber assay. Conversely, following the analysis of 52 hepatoma patients, Chen et al (38) reported that immunohistochemical α-Klotho staining was significantly associated with liver cirrhosis, tumor multiplicity and venous invasion, and the survival rate of subjects with high α-Klotho expression was significantly decreased compared to patients with low α-Klotho expression.…”
Section: Discussionmentioning
confidence: 91%
“…In vitro studies showed that aKlotho induces autophagy in cancer cell lines. 44,82 The in vivo effects of aKlotho on autophagy in intact animals have not been described. We showed that autophagic activity is upregulated in Tg-Kl mice at baseline as evidenced by significant p62 reduction and mild increase in LC3-II formation compared with in WT mice.…”
Section: Discussionmentioning
confidence: 99%
“…[38][39][40] Associations between the levels of autophagy and aKlotho have previously been reported, but the results were not consistent. [41][42][43][44] Furthermore, whether the renoprotection rendered by aKlotho is related to modulation of autophagy has not been studied.…”
mentioning
confidence: 99%